Differences in Fishing Time for By-Catch in Gill Net Fishing Gear in Selayar Waters - serang, Abu samad; Almohdar, Erna; Hukubun, Wiwien G.; Anwar, Yanto; Tanjaya, Erwin; Marasabessy, Fatmawati (Agrikan Jurnal Agribisnis Perikanan, 2024)
This research was conducted from October to December 2022, located in Selayar Village, Southeast Maluku Regency. The aim of this research is to determine the main, by-catch and discarded catches and to determine the differences between morning and afternoon catches. The method used in this research is the experimental metal fishing method, namely, conducting direct observations in the field of the catch using gill net fishing gear, then identifying the type of fish for each catch, counting the number of fish and weighing the weight of the fish (kg). ). The method used is experimental fishing or experimental fishing, observation and interviews. the object used is the catch on the gill net fishing gear. The research results are described in graphical form. The research results showed the highest value of main catch during the day, by-catch during the day and discard catch also during the day.